Preferred communication channels for office building energy conservation behaviour - Mohd. Basri Baharan, Mastura (2014)
In Malaysia, the usage of energy is high especially in commercial sector. The office building energy usage is among the main contributors to the country’s energy use. National Energy Balance (2012) stated that commercial sector is the second higher which contributed 33.2% of energy usage after industry 45.1% and followed by residential sector of 21.2%. One of the major challenges faced by facilities manager is to reduce the building’s energy consumption. Although there are previous energy conservation programs launched, the energy conservation progress in government office building still lacking behind. To improve office building user’s energy conservation behaviour effectively, selection of right communication channels then distributes energy conservation messages with the right communication channels remains an important strategy. This study has two objectives. The first objective is to identify the suitable types of communication channel as a medium to deliver information message. Expert’s interview was conducted to identify the suitable communication channel in the context of office building. Responses gathered from experts use to formulate survey instrument to achieve second objective. The second objective is to identify preferred communication channels to foster office building energy conservation behaviour. To achieve objective two, the questionnaire was developed based on literature review and expert’s interview and distributed to office building staffs in Putrajaya. A total of 525 convenience sample were gathered and analyzed using choice based conjoint analysis (CBC). Five types of communication channels were identified: dialogue oriented approach, mass media, print media, outdoor media and audio visual media. The results showed that the most preferred types of communication channel is mass media while the least preferred is audio visual media. This study then proposed suggestions for the future research.